Fast trains, slow boats, and the ancestry of the Polynesian islanders - OPPENHEIMER, STEPHEN; RICHARDS, MARTIN (Science progress (1916), 2001)
The question of the origins of the Polynesians has, for over 200 years, been the subject of adventure science. Since Captain Cook's first speculations on these isolated Pacific islanders, their language affiliations have been seen as an essential clue to the solution. The geographic and numeric centre of gravity of the Austronesian language family is in island Southeast Asia, which was therefore originally seen as their dispersal homeland. However, another view has held sway for 15 years, the 'out of Taiwan' model, popularly known as the 'express train to Polynesia'. This model, based on the combined evidence of archaeology and linguistics, proposes a common origin for all Austronesian-speaking populations, in an expansion of rice agriculturalists from south China/Taiwan beginning around 6,000 years ago. However, it is becoming clear that there is, in fact, little supporting evidence in favour of this view. Alternative models suggest that the ancestors of the Polynesians achieved their maritime skills and horticultural Neolithic somewhere between island Southeast Asia and Melanesia, at an earlier date. Recent advances in human genetics now allow for an independent test of these models, lending support to the latter view rather than the former. Although local gene flow occurring between the bio-geographic regions may have been the means for the dramatic cultural spread out to the Pacific, the immediate genetic substrate for the Polynesian expansion came not from Taiwan, but from east of the Wallace line, probably in Wallacea itself.